PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT TERHADAP KINERJA KEUANGAN DENGAN SISTEM PENGUKURAN KINERJA SEBAGAI VARIABEL MODERASI PADA CV MUTIARA ABADI SEMARANG - Nindiya Sidha Kumala; M. Th Heni Widyarti (Politeknik Negeri Semarang, 2020)
The optimal application of TQM must be followed by the application of elements from the management accounting system, one of which is the performance measurement system because it can help the achievement of strategic objectives and short-term goals of the company. This research aims to analyze the effect of implementing Total Quality Management on financial performance with a performance measurement system as a moderating variable on CV Mutiara Abadi Semarang. Data analysis method used is Moderated Regression Analysis to determine the effect of moderating variable. This research shows that Total Quality Management has a significant effect on financial performance, the performance measurement system has no significant effect on financial performance and the performance measurement system does not moderate the relationship between Total Quality Management and financial performance.